Analisis Kinerja Struktur Atas Gedung 7 lantai Dengan Variasi Dimensi dan Lokasi Shearwall Studi Kasus Konsep Kondominium Hotel - Muhammad Ismail (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
The final project consists of modifications condominium building with a wide range of alternatives. Condominium hotel is that every hotel room or unit can be owned and traded by individuals. Condominium which has been called the apartment can be operated like a tourist accommodation. A wide variety of alternative building contains about modification alternatives A condominium hotel is an existing building of condominium hotels, alternative B uses modified by adding shearwall angle on the corner of the building, alternative C using shearwall modified by adding